IgA Vasculitis Associated with COVID-19 Infection Successfully Treated with Corticosteroid Regimen without Relapse - Davis, Samantha (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.